Defining the impact of vascular risk factors on erectile function recovery after radical prostatectomy. (3rd July 2012) - Teloken, Patrick E.; Nelson, Christian J.; Karellas, Michael; Stasi, Jason; Eastham, James; Scardino, Peter T.; Mulhall, John P.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Erectile function recovery after radical prostatectomy is affected by surgical technique and patient factors. Age and preoperative erectile function are the 2 patient factors that have been consistently shown to impact postoperative erectile function. The presence of vascular risk factors preoperatively seems to negatively impact erectile function recovery after radical prostatectomy independently from age, preoperative erectile function and surgical technique. Objective To examine whether vascular risk factors (VRFs) affect erectile function (EF) recovery after radical prostatectomy (RP). Patients and Methods From our prospective database we identified patients with clinically localised prostate cancer who had undergone RP and had preoperative information on EF and VRFs (hypertension, hypercholesterolaemia, diabetes mellitus, coronary artery disease [CAD], and cigarette smoking), surgeon‐graded nerve‐sparing status, and EF data collected between 24 and 30 months after RP. Results In all, 984 patients were included in the analyses. The frequency of the VRFs was as follows: hypertension (38%), hypercholesterolaemia (36%), diabetes mellitus (7%), CAD (5%), and cigarette smoking (37%). On univariate analysis, EF between 24 and 30 months was associated with age (r = 0.37, P < 0.001), EF before RP (r = 0.41, P < 0.001), NSS (r = 0.35, P < 0.001), and VRFs (0–2 vs >3 VRFs; r = 0.15, P = 0.003). On multivariable analysis all variables remained statistically significant, and accounted for 28% of the total variance in EF between 24 and 30 months after RP. Conclusions The presence of VRFs seems to adversely affect EF recovery after RP independently of other factors. This observation might be useful for improving patient counselling before treatment and to support the development of new treatment strategies for erectile dysfunction after RP.